Program PHBS di Masjid Tuntungan Dalam Mewujudkan Jamaah yang Prodduktif Dalam Peduli Sehat - Vaudi, Tazkia; Riski, Mutiara; Praramadhani, Nikita; Nabilla, Maisya; Al Afghani, Zaid; Mardiyah, Atika; Hasibuan, Dinda Syahfitri; Darma, Eka Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve optimal health status for everyone. The implementation of PHBS in the mosque environment is one of the efforts to mobilize and empower the administrators and also the congregation of the mosque to live a clean and healthy life. The purpose of this research is to realize the PHBS program at the Tuntungan mosque so that congregations can be productive in caring for health. The method used in this study is qualitative and data collection techniques by means of interviews, observation and documentation. The results based on the results of research on cleanliness in the Tuntungan mosque environment are quite clean, but there are still many people who pay less attention to cleanliness and also the condition of the water in the mosque still feels rusty. The conclusion of this study is that there are still many mosque congregations who have not implemented PHBS at the Tuntungan mosque. Keywords: PHBS, Mosque